Nautical Charts of the Brazilian Coast for Small Craft - Lira, Eliana Fernandez; Amadeo, Fernando (The International Hydrographic Review, 2018)
Brazil, a country of continental dimensions, with a coastline of approximately 4,000 nautical miles in length, which includes numerous beaches and bays of considerable natural beauty, is ideally suited for small craft navigation. According to a recent survey, the total number of small craft registered in Brazil is around 30,000, involving over 100,000 people, which, for a developing country, is a large number. This great number of users justifies the preoccupation of the Directorate of Hydrography and Navigation (DHN) regarding the safety of yachtsmen and the consequent production of special nautical charts. Since 1988, the Directorate has been promoting an annual Seminar on Safety of Navigation, in which a working group, composed of representatives from yachting and naval organizations has dedicated itself exclusively to this activity. Due to the stated requirements of the usersfor a cartographic document suitable for use within the limited space of small craft, DHN, based on proposals presented by the working group, has made a contract with a Brazilian private company for the production of these charts. This paper describes the production of such charts, from the planning phase and data collection to their acceptance by DHN as cartographic documents, intended for small craft navigation.